Assessment of Patterns of Neuropathy in Patients with Newly Diagnosed Type II Diabetes Mellitus - Mahmood, Hafiz Abad; Muhammad Uthman; Virk, Muhammad Abdulrehman; Shahbaz, Ali; Naseem, Nawal; Gul, Mehak (Indus Journal of Bioscience Research, 2025)
Background: Diabetic peripheral neuropathy is a known complication of type 2 diabetes mellitus (T2DM), with additional evidence to support the existence of the neuropathy among newly diagnosed patients. This research evaluated peripheral neuropathy occurrence along with intensity in newly identified T2DM patients alongside investigating their demographic-related neuropathy relationships. Objective: To determine the frequency and patterns of peripheral neuropathy in patients with newly diagnosed type 2 diabetes mellitus. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from October 2024 to March 2025 at the Department of Medicine, Sheikh Zayed Hospital, Lahore. Methodology: A total of 350 patients, aged from 25 to 75 years, with newly diagnosed T2DM in the previous 6 months were enrolled. Demographic data, including age, gender, height, weight, BMI, and medical history was also recorded. Peripheral neuropathy was assessed using a biothesiometer to measure the Vibratory Perception Threshold (VPT), with values greater than 15 volts indicating neuropathy. Results: The prevalence of peripheral neuropathy was found to be 48.9%, with 40.9% of patients having mild symptoms, 14% moderate, and 45% severe symptoms. Notably, patients aged over 50 showed a higher prevalence of neuropathy (67.1%). Gender differences were also observed, with more females (60.9%) affected compared to males (41.5%). Conclusion: This study highlights the high prevalence of peripheral neuropathy in newly diagnosed T2DM patients, with age, gender, and duration of diabetes serving as significant predictors.